Carbon monoxide concentrations in infant deaths. Issue 4 (April 1987) - Variend, S; Forrest, A R
Abstract : Carboxyhaemoglobin measured in 50 infant deaths showed no significant difference between home and hospital deaths nor between explained and unexplained deaths. Carbon monoxide toxicity is unlikely to have an important role in the pathogenesis of sudden infant deaths. The generally low carboxyhaemoglobin concentrations are probably due to endogenous production.